Electronic participation : 10th IFIP WG 8.5 International Conference, ePart 2018, Krems, Austria, September 3-5, 2018, Proceedings /: 10th IFIP WG 8.5 International Conference, ePart 2018, Krems, Austria, September 3-5, 2018, Proceedings. (2018) - Unknown
No abstract available